ANAK BERKEBUTUHAN KHUSUS DALAM NOVEL HOUSE RULES KARYA JODI PICOULT - Awaludin, Taufiq (Jurnal Penerjemahan, 2014)
This study aims to describe the efforts of House Rules, a Jodi Picouli's novel, in defending a child with special needs who suffers from developmental disorder, namely autistic spectrum disorder. By assigning a novel as his object of study, the researcher determines the psychology theory relevant with the scope of his study. The result of the study shows that the author has made a detailed description of the development disorder that Jacob is afflicted with, which is in accordance with the theory of Greenspan and other experts. Hence, the researcher concludes that this novel could also serve as a source of preliminary information for those people who are yet familiar with the Asperger syndrome.